SOME ASPECTS REGARDING TRANSLATION DIVERGENCES BETWEEN THE AUTHENTIC TEXTS OF THE EUROPEAN UNION - Laura-Cristiana SPĂTARU-NEGURĂ (Challenges of the Knowledge Society)
When multiple legal orders and languages co-exist within a single legal regime, there is potential for divergences between the legal texts. The European Union represents on the international legal stage, the most ambitious linguistic project, integrating 28 Member States and 24 official languages. What we undertook with this study was to discover how the multilingual and multicultural environment of the European Union affects its legislative and judicial processes. We tried to argue the problem of translation divergences between the authentic texts of the European Union. Many questions arise. Is ‘controlled multilingualism’ the key to our problem? Is weak multilingualism the solution - especially that it is not new for the European construction? Should one language be chosen as the original? Of course that we have to see that multilingualism is an advantage, a blessing of the European Union and not an obstacle, a curse. We consider that, despite the various problems with the European multilingualism described in this study, it is unlikely that something would change in the foreseeable future. However, we consider that lawyers should research more in languages and legal interpretation. Interdisciplinary efforts could solve the multilingualism problems of the European Union. The present study is part of a more complex research on this theme and it is meant to approach certain important points of the master thesis prepared in Switzerland for a LL.M. program.